Sports technologies assisting in sport (Revista Brasileira de Contabilidade e Gestão, 2013)
This article aims to present to the reader an idea of the use of technology and in what ways it can be useful, both for athletes, with software that helps to improve their performance and treat injuries, as well as for coaches, with this technology to develop new strategies, and for referees, to help them to promote a fairer and more competitive game. Data were collected by the questionnaire technique with 7 open and 1 closed questions, made with regulars of Planeta Korpo academy in Ibirama, state of Santa Catarina (SC), the results achieved are within expectations, since the subject is well-disseminated and many already know the importance of technology in sport.
Keywords: performance; software; technology; treatment; Aid